Andragogy of Local Regulations for No Smoking Areas in Bagan Deli Village - Suhaidi; Sunarmi (Talenta Publisher, 2021)
Andragogy of Regional Regulation on No-Smoking Areas is focused on creating non-smoking areas in Bagan Deli Village. The process to involve adult students in a learning experience structure is certainly focused on the community in the Bagan Deli Kelurahan as a community unit that is expected to be able to understand the existence of a non-smoking area as an implementation of the No Smoking Area Regional Regulation No. 3 of 2014. Activities are based the situation in the neighborhood around Kelurahan Bagan Deli where there are still people who smoke in public places or in public facilities such as schools, hospitals, places of worship or in public transportation. The Bagan Deli Village community will be given an understanding of the existence of areas without smoking, knowing which public facilities are not allowed to smoke by attaching signs such as